Implementation of Samarinda Mayor Regulation Number 18 of 2022 Concerning Supervision and Application Of Administrative Sanctions for Waste Management in Samarinda City (Case Study in Samarinda City District) - Ramadhani, Ramadhani; Friska Prasyta Harlis (Jurnal Multidisiplin Sahombu, 2025)
This study was conducted to examine the implementation of Samarinda Mayor Regulation Number 18 of 2022 concerning Supervision and Implementation of Administrative Sanctions in Waste Management in Samarinda City, with a focus on the Samarinda City District. The background to this policy is increasingly complex environmental problems, particularly the high volume of waste and the low level of public participation and awareness of the importance of orderly waste management. This study uses a qualitative descriptive approach with data collection techniques such as observation, in-depth interviews, and documentation. The focus of the analysis uses the policy implementation theory by G. Shabbir Cheema and Dennis A. Rondinelli, which includes four main indicators: environmental conditions, inter-organizational relationships, organizational resources, and the characteristics and capabilities of implementing agents. The data analysis technique uses the interactive model by Miles, Huberman, and Saldana, which involves the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of this policy has generally been running, but is still not optimal. In terms of environmental conditions, it was found that public awareness of disposing of waste in the appropriate place and at the appropriate time is still low. Coordination between implementing agencies, such as the Environmental Agency, sub-districts, urban villages, and neighborhood associations (RT/RW) has not been optimal. Resources, both human resources and supporting facilities such as transportation facilities and temporary disposal sites, remain limited. Meanwhile, policy implementers in the field are deemed not fully prepared, both in terms of policy understanding, technical skills, and ability to address community resistance. Based on these findings, it can be concluded that the successful implementation of this Mayoral Regulation is largely determined by the synergy between institutional strengthening, capacity building of implementers, resource availability, and the development of environmental awareness and a culture of order among the community.